The Effect of Information Level and Coping Style on Pain and Anxiety in Needle Liver Biopsy - Nir Hilzenrat; Rose Yesovitch; Ian Shrier; Maria Stavrakis; Marc Deschênes (Canadian Journal of Gastroenterology)
Biopsy of the liver is an important diagnostic procedure. The procedure is invasive and may be painful for patients. Sedative drugs are not used because the associated drop in blood pressure mimics hemorrhage, a major complication of the procedure. Cognitive and behavioural techniques have been used to decrease stress in patients undergoing other medical procedures. In the present study, it is postulated that providing procedural and sensory information may reduce patient anxiety levels. Patient coping styles were evaluated and anxiety and pain levels were assessed by using a visual analogue scale. Subjects were randomly assigned to one of two groups. The control group received basic information about the procedure. The experimental group received the same basic information followed by more detailed educational information. Subjects also filled out the Krantz Health Opinion Survey, a short questionnaire used to classify coping styles as either information-seeking or information-avoiding. Seventy-five subjects (38 control and 37 experimental) with similar demographics were included in the present study. No significant differences were found in anxiety levels or pain levels 30 min and 6 h postbiopsy. There was also no significant difference between groups once coping style was added into the analysis. The study failed to show any advantage in providing additional information to subjects before liver biopsy, regardless of coping style.